Business Confidence and the Economic Activity in South Africa - Kutu, Augustine Adebayo; Ngalawa, Harold; Nzimande, Ntokozo (Journal of Ecohumanism, 2024)
The objectives of this study are: to examine the impact of business confidence on economic activity in South Africa; to determine whether the indicator of business confidence can predict movements of economic activity over business cycles, and to forecast business confidence and economic activity in South Africa. Employing a Vector Autoregressive model and data from 1994Q1 – 2019Q4, we find that business confidence can predict the direction of economic activity in South Africa. It is also revealed that an increase in the level of business confidence can lead to an increase in economic growth and reduce unemployment rate. The result from the forecasting analysis indicate that economic agents can monitor the current economic situation and future direction of output growth. We recommend that policymakers should include the business confidence index as a policy tool in tracking the performance of economic activity due to its significant role in predicting economic downturns.